Recurrence of atrial fibrillation after cardiac surgery: long-term evidence from cardiac devices - Swinn, Tim; Pezard-Snell, Marius; Brain, Lauren; Dimitropoulos, Gerasimos; Dastidar, Amardeep; Sammut, Eva; Barman, Palash (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAtrial fibrillation (AF) after cardiac surgery occurs in 20%–40% of cases and is associated with significant morbidity. Studies have shown an association with immediate postoperative AF (POAF) and recurrent AF; however, to our knowledge, no trials have used continuous electrogram monitoring data from cardiac devices (pacemakers or defibrillators) to assess the rate of long-term AF recurrence.MethodsUsing institutional databases, we identified patients with a cardiac device who underwent coronary artery bypass grafting (CABG) and/or a procedure on their aortic valve (AV) or mitral valve (MV) between January 2011 and March 2020. POAF and comorbidities were assessed using the electronic patient record, and recurrent device-detected AF was defined as any episode of AF lasting >6 min on device check between 6 weeks and 18 months postoperatively.ResultsPOAF was associated with recurrent device-detected AF (n = 85, odds ratio 3.26, 95% confidence interval 1.19–8.97, p = 0.02). Age was an independent risk factor for developing POAF (n = 302, p = 0.033), and MV surgery had a higher rate of POAF than CABG alone (54% vs. 32%, p = 0.047) and AV surgery (54% vs. 34%, p = 0.048). Forty-four per cent of patients developing POAF were discharged on oral anticoagulation (OAC).DiscussionPostoperative is associated with a threefold greater odds of developing recurrent device-detected AF: it is not a simple transient phenomenon. Larger prospective studies are required to identify which patients would benefit from heart rhythm surveillance and whether OAC is an effective treatment in this patient group.